2nd generation biomass derived glucose conversion to 5-hydroxymethylfurfural and levulinic acid catalyzed by ionic liquid and transition metal sulfate: Elucidation of kinetics and mechanism. (20th May 2020) - Kumar, Komal; Pathak, Shailesh; Upadhyayula, Sreedevi
Abstract: The conversion of 2 nd generation biomass to 5-HMF and LA is a promising route for the production of key platform chemicals and renewable fuels. This work reports a clean synthesis of levulinic acid (LA) and 5-hydroxymethyl furfural (5-HMF) from waste biomass derived glucose in aqueous phase using –SO3 H functionalized ionic liquid (IL) catalyst [IL-SO3 H][Cl] and nickel sulfate (NiSO4 .6H2 O) co-catalyst. A 99.92% maximum glucose conversion was achieved with 56.37% LA selectivity at 155 °C and 5 h reaction time. The 5-HMF yield was 21.8% at 175 °C and 1.5 h reaction time. The calculated synergy factor of catalyst and co-catalyst indicates synergistic effect which resulted in the high glucose conversion with high LA yield (56.33%). To elucidate the kinetics and reaction mechanism, a series of the reactions were performed in a batch reactor in the temperature range 145 °C–175 °C. Based on the product distribution, a kinetic model for the glucose conversion and LA formation reaction was derived following the key reaction steps: (1) glucose conversion into 5-HMF; (2) humin formation from glucose conversion; (3) 5-HMF conversion into LA; (4) humin formation from 5-HMF. The experimental results were fitted well to a pseudo-first order model of the reaction network. The calculated activation energy ( E a ) for the glucose conversion to 5-HMF and LA was found to be 47.45 k J / m o l and 34.28 k J / m o l, respectively. In this study, detailed kinetics and parameter estimation by developing the phenomenological model from the product distribution and reaction network of glucose to LA and 5-HMF is reported. Graphical abstract: Image 1 Highlights: IL with NiSO4 .6H2 O gave 99.92% glucose conversion with 56.37% LA selectivity. Synergistic effect of the mixed acid system and reaction mechanism is described. Pseudo-first order kinetics for glucose conversion to levulinic acid was modeled. Lower activation energy (34.28 k J / m o l ) was observed for glucose conversion to LA.